Revisiting Research Methods in Language Learning Psychology From a Complexity Dynamic System Theory Perspective - Yang, Jianbo (Frontiers in Psychology, 2021)
Language learning is a dynamic and complex process in which different factors and variables are constantly interacting. However, many studies done on constructs related to teacher-learner psychology have used one-shot quantitative research designs, while it is impossible to capture the complexity and dynamism of such variables via one-time measurements. Against this gap, complexity dynamic system theory (CDST) has recently been applied to explore processes and changes that a construct may undergo. To shed more light, the present study examined the current research methods used in this research domain and presented the contributions and different conceptualizations that can be made through CDST. In the end, some implications and future directions are suggested for passionate scholars.